Ewolucja biznesu międzynarodowego jako dyscypliny naukowej w dobie globalizacji gospodarki - Drelich-Skulska, Bogusława (Evolution of International Business' Discipline in the Global Economy, 2008)
In the 20th century the international business field (IB) was developing dynamically. The widespread development of internationalization and liberalization processes as well as information and telecommunication technologies in the 1990s caused researchers in international business to pay more attention to a variety of new factors affecting this field of study. The analysis of the IB theoretical framework and the observation of economic processes going on globally allow us to specify future strategies for this field of study. The most important ones are: comparative research, emerging markets, emerging locations, virtual firm, global branding and distribution, impact of MNEs on host economy. Furthermore, it should be underlined that the interest in international business is increasingly growing in plenty of research centers - not only in the Triad but also in the Asia-Pacific Region and Central-Eastern Europe.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 59-67